2004
DOI: 10.1079/phn2003516
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of diet quality

Abstract: Background: An unbalanced diet is a main risk factor for several chronic diseases. This paper identifies groups of individuals with an unbalanced diet based on the consumption of nutrients. A characterisation of the groups may help to focus efforts aimed at improving the dietary behaviour of the population. Methods: Using nutritional data of 1763 men and 2267 women participating in the German Nutrition Survey of 1998, we constructed two indices for diet quality that each combines a large amount of nutrients in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
93
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(109 citation statements)
references
References 15 publications
(20 reference statements)
9
93
1
2
Order By: Relevance
“…Several epidemiological studies reported a direct association between diet quality and healthy lifestyle variables (Ruidavets et al, 2004;Thiele et al, 2004;Tur et al, 2004). In the present population, participants with a high adherence to low-energy density diets showed a trend towards a healthier lifestyle characterized through a higher degree of physical activity during leisure time, lower prevalence of smoking, sedentary lifestyle and alcohol consumption.…”
Section: Discussionmentioning
confidence: 53%
“…Several epidemiological studies reported a direct association between diet quality and healthy lifestyle variables (Ruidavets et al, 2004;Thiele et al, 2004;Tur et al, 2004). In the present population, participants with a high adherence to low-energy density diets showed a trend towards a healthier lifestyle characterized through a higher degree of physical activity during leisure time, lower prevalence of smoking, sedentary lifestyle and alcohol consumption.…”
Section: Discussionmentioning
confidence: 53%
“…The QFFQ was completed for foods eaten over the previous 30 d. The food intake was coded according to the South African Food Composition Database System of the South African Medical Research Council and then used to calculate the nutrient and food group intakes (23)(24)(25) . Table 1 presents the components and cut-off points of the HDI (13) and the Deficiency Score/Excess Score by Thiele et al (12) , which were used in the present study. The score by Thiele et al suggested using up to thirty nutrients in a Deficiency Score to identify a preferable diet quality and using six nutrients in an Excess Score to identify a nonpreferable diet quality.…”
Section: Methodsmentioning
confidence: 99%
“…In a further step, the nutrient intake data of the European adolescents were condensed to a single parameter, the Nutritional Quality Index (NQI), to assess overall diet quality (25) . The NQI was constructed on the basis of nutritional recommendations as evaluation criteria (26) and was used as a summary measure of the degree to which the adolescents' diet conformed to the D-A-CH recommendations.…”
mentioning
confidence: 99%